Neuroprotective and Antioxidant Effect of Naringenin-Loaded Nanoparticles for Nose-to-Brain Delivery - Md, Shadab (Brain Sci, 2019)
Parkinson’s disease (PD) is a neurodegenerative disorder resulting in a decreased nigrostriatal availability of dopamine. Oxidative stress is one factor contributing to PD. Naringenin (NAR), a flavonoid, is a potent antioxidant shown to be beneficial in experimental PD. The clinical development of NAR has been hampered due to its low bioavailability resulting from gastrointestinal degradation, inefficient permeability, and low aqueous solubility. The objective of the present research was to formulate and characterize naringenin-loaded chitosan nanoparticles (NAR NPs) for nose-to-brain delivery. The cellular uptake, cytotoxicity, and neuroprotective effects of NAR NPs were determined using the SH-SY5Y cell line in vitro. NAR NPs were prepared using the ionic gelation method and characterized by zetasizer, transmission electron microscopy (TEM), and field emission microscopy (FESEM). The average particle size, polydispersity index (PDI), zeta potential, entrapment efficiency, and 24 h in vitro release profile were 87.6 ± 8.47 nm, 0.31 ± 0.04, 15.36 ± 2.05 mV, 91.12 ± 2.99%, and 54.80 ± 4.22%, respectively. The percentage NAR permeation through nasal mucosa from NPs was found to be 67.90 ± 0.72%. Cellular uptake of prepared NPs was confirmed by fluorescence microscopy. Neuroprotective activity of NAR NPs was evaluated through viability assays and by estimating reactive oxygen species (ROS) levels. NAR NPs showed enhanced neuroprotective ability and antioxidant effect against 6-OHDA-induced neurotoxicity in SH-SY5Y cells. However, animal studies are necessary to establish the potential of NAR NPs to be an effective carrier for the treatment of PD for nose-to-brain delivery.